Agent-based evolutionary optimisation of trading strategies. (21st February 2008) - Ni, Jiarui; Luo, Dan; Ou, Yuming; Luo, Chao
The backtesting and optimisation of trading strategies has emerged as an interesting research and experimental problem in both finance and Information Technology (IT) fields. However, it is a non-trivial task to effectively and efficiently optimise trading strategies, not to mention the optimisation in the real-world situations. This paper discusses the application of evolutionary technologies (genetic algorithm in particular) to the optimisation of trading strategies. Experimental results show that this approach is promising. Due to the complexity involved in the optimisation process, we further present an agent-based system that can help users easily specify and execute optimisation jobs to their advantages.